Smartphone locations reveal patterns of cooling center use as a heat mitigation strategy. (January 2023) - Derakhshan, Sahar; Bautista, Trisha N.; Bouwman, Mari; Huang, Liana; Lee, Lily; Tarczynski, Jo; Wahagheghe, Ian; Zeng, Xinyi; Longcore, Travis
Abstract: The increasing frequency and duration of extreme heat events prompts questions regarding mitigation proposals and evaluation of current strategies such as cooling centers. Cooling centers may be formally designated or informally used spaces such as indoor shopping centers that the public use as a refuge from heat. Smartphone location data show how a sample of the population moves during the day, what behavioral adjustments they apply in response to heat events, if cooling centers are being used, what factors correlate with use, and whether centers are serving vulnerable populations. We compared spatial patterns of smartphone locations in Los Angeles County between paired extreme heat days and control days (n = 12) in summer 2017. Cooling centers were used 1.1–1.7 times longer during heat events, depending on type, with formal cooling centers used longer. Informal centers, however, were used more (90% of visits). Distance to nearest public transit stop was inversely related to the number of center visits. Vulnerable communities, as measured by the Social Vulnerability Index (SoVI), used centers located in neighborhoods with higher vulnerability scores more. Use of smartphone data to assess activity space of individuals has substantial potential for evaluating mitigation strategies in the face of increasing extreme heat events. Highlights: Mobile phone users' activity space data provides an assessment of cooling center use as a heat mitigation strategy. Comparison of data from hot versus control days shows longer visits in cooling centers of Los Angeles County on hot days. Cooling center visitors are from neighborhoods with higher proportions of elderly, Asian, and Hispanic residents. Informal commercial spaces like shopping centers are used more frequently as a heat refuge than formal cooling centers. Residents of vulnerable neighborhoods visit centers more on hot days, but their visits drop as their distance increases.